Early life nutrition influences susceptibility to chronic inflammatory colitis in later life - Ley, Delphine (Sci Rep, 2019)
The first thousand days of life are a critical time of development in humans during which the risk profile for diseases in later life can be modified. Nevertheless, long-term consequences of early environment on susceptibility to intestinal diseases have not yet been assessed. Using a mouse model of postnatal growth restriction (PNGR), we showed that early life nutrition influences intestinal maturation and gut health in later life. PNGR induced an alteration of the intestinal barrier in pups at weaning, resulting in increased intestinal permeability, and affected gut bacterial colonization. Specifically, pups with PNGR harbored a decreased bacterial diversity, higher Enterococcus spp., Staphylococcus spp., and Escherichia-Shigella spp., and lower Odoribacter spp. and several members of the Lachnospiraceae family. The lack of an efficient intestinal barrier in early life and the dysbiosis induced by PNGR were associated with a higher susceptibility to chronic colitis in adulthood.